What is the role of putrescine accumulated under potassium deficiency?. (19th February 2020) - Cui, Jing; Pottosin, Igor; Lamade, Emmanuelle; Tcherkez, Guillaume
Abstract: Biomarker metabolites are of increasing interest in crops since they open avenues for precision agriculture, whereby nutritional needs and stresses can be monitored optimally. Putrescine has the potential to be a useful biomarker to reveal potassium (K + ) deficiency. In fact, although this diamine has also been observed to increase during other stresses such as drought, cold or heavy metals, respective changes are comparably low. Due to its multifaceted biochemical properties, several roles for putrescine under K + deficiency have been suggested, such as cation balance, antioxidant, reactive oxygen species mediated signalling, osmolyte or pH regulator. However, the specific association of putrescine build‐up with low K + availability in plants remains poorly understood, and possible regulatory roles must be consistent with putrescine concentration found in plant tissues. We hypothesize that the massive increase of putrescine upon K + starvation plays an adaptive role. A distinction of putrescine function from that of other polyamines (spermine, spermidine) may be based either on its specificity or (which is probably more relevant under K + deficiency) on a very high attainable concentration of putrescine, which far exceeds those for spermidine and spermine. putrescine and its catabolites appear to possess a strong potential in controlling cellular K + and Ca 2+, and mitochondria and chloroplasts bioenergetics under K + stress. Abstract : Putrescine accumulates under potassium deficiency but its exact role in plants remains unknown. Here we review the various effects of putrescine on ion transport and metabolism. The current evidence supports a model in which putrescine mitigates the effects of increased calcium under K deficiency.